Grey filter functions for suppression of grey-scale elements. Issue 2 (1st February 2019) - Wei, Tieping; Yang, Xiaoxiang; Chen, Chuifu; Yao, Jinhui; Lian, Guofu
ABSTRACT: To solve the problem of the presence of grey-scale material in optimization results and improve convergence efficiency during the optimization procedure caused by those intermediate densities, three kinds of simpler filter functions were proposed for the variable density method according to S-curve models. First, the feasible range for the parameters of the filter functions was determined by studying Messerschmitt–Bölkow–Blohm beam with the solid isotropic micro-structure with the penalization (SIMP) method. Then, the filter functions were applied to three classic examples to verify their validity and feasibility. The results showed that higher convergence efficiency, clearer structure boundaries, and better feasible solutions were obtained compared with that without the filter function. Finally, the filter functions were also compared with one existing method to demonstrate its effectiveness and validity.